2014
DOI: 10.1080/21501203.2014.928386
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide survey of the secondary metabolite biosynthesis genes in the wheat pathogenParastagonospora nodorum

Abstract: The model pathogen Parastagonospora nodorum is a necrotroph and the causal agent of the wheat disease Septoria nodorum blotch (SNB). The sequenced P. nodorum genome has revealed that the fungus harbours a large number of secondary metabolite genes. Secondary metabolites are known to play important roles in the virulence of plant pathogens, but limited knowledge is available about the SM repertoire of this wheat pathogen. Here, we review the secondary metabolites that have been isolated from P. nodorum and rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 125 publications
(154 reference statements)
2
38
0
Order By: Relevance
“…We previously performed a detailed survey of the P. nodorum genome for secondary metabolite genes and have compiled the polyketide synthase (PKS) gene inventory for this wheat pathogen (50). To identify the PKS gene encoding AOH in P. nodorum, we first searched for P. nodorum PKSs that are homologous to PksH and PksJ, which were previously implied to be involved in AOH production in A. alternata by RNA interference (RNAi) silencing experiments (36).…”
Section: Resultsmentioning
confidence: 99%
“…We previously performed a detailed survey of the P. nodorum genome for secondary metabolite genes and have compiled the polyketide synthase (PKS) gene inventory for this wheat pathogen (50). To identify the PKS gene encoding AOH in P. nodorum, we first searched for P. nodorum PKSs that are homologous to PksH and PksJ, which were previously implied to be involved in AOH production in A. alternata by RNA interference (RNAi) silencing experiments (36).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous survey of the P. nodorum genome showed that it encodes at least 38 secondary metabolite gene clusters. The key secondary metabolite backbone biosynthesis genes found in these clusters include 23 polyketide synthase (PKS) genes and 14 non‐ribosomal peptide synthetase (NRPS) genes, four terpene synthases and five prenyltransferases (Chooi et al ., ). Previous transcriptomics data has shown the up‐regulation of several secondary metabolite gene clusters during various stages of in planta growth (Ipcho et al ., ; Chooi and Solomon, ).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the SN477 sequence showed that it encodes a typical partially reducing (PR) PKS with ␤-ketosynthase (KS), acyltransferase (AT), dehydratase (DH), ketoreductase (KR), and acyl career protein (ACP) domains (7,(29)(30)(31). Among the characterized fungal PKSs, SN477 was the most similar to the partially reducing PKS ATX from Aspergillus terreus, which synthesizes 6-methylsalicylic acid (6-MSA) (32).…”
Section: Snog_00477 Is the Most Highly Expressed Pks Gene In Plantamentioning
confidence: 99%
“…Along with the tailoring biosynthesis genes, they formed a total of 38 secondary metabolite gene clusters in P. nodorum. So far, none of the products of these secondary metabolite gene clusters have been identified, and only a few secondary metabolites have been identified in this species (7). These metabolites include (R)-mellein and derivatives (8,9), septorines (10,11), mycophenolic acid (8), alternariol (12), and (ϩ)-4=-methoxy-(2S)-methylbutyrophenone (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation